Kapitalisasi Pendidikan Serta Dampaknya Bagi Pendidikan Islam - Rahmah Rahmah; Kasful Anwar US; Sya'roni Sya'roni (Jurnal Budi Pekerti Agama Islam, 2024)
This study discusses the capitalization of education and its impact on Islamic education, with a discussion of what is the definition of capitalization of education, Islam's view of capitalization of education, and the impact of capitalization of education on Islamic education. Education is an effort to educate humans to become a complete human being. Education is a forum to provide assistance to students to become more mature. Islamic education is a conscious guidance or leader by educators towards the physical and spiritual development of students towards the formation of their main personality (insan kamil). Capitalism in education means the capitalization of education, which is the process of capitalizing on education. Where the principles of the market economy, such as competition, profitability, and privatization, have a significant effect on the education system. In this context, education is seen as a market where a commercial approach is applied to manage, finance, and provide educational services.